State of the Nation's Health Report - School of Public Health (University of Ghana, 2018)
This report serves as a physical representation of the long-standing collaboration between University of Ghana School of Public Health and the state agencies responsible for health delivery – Ministry of Health and Ghana Health Services. Staff from these three institutions have worked together to review varied publications and datasets related to the health of Ghanaians and have produced this comprehensive review on health in Ghana. The state of health in Ghana is covered by many different sources, including service reports from the Ghana Health Service, policy documents from the Ministry of Health, academic publications in peer-reviewed journals and reports from donor agencies. Even for experienced and established researchers, going through all this primary material in order to answer a question can be a daunting task. It is however important that all these sources be consulted and evaluated in order to have a clear picture of the current situation, The State of the Nations Health Report will serve as a one stop destination for students, researchers, teachers and policy makers who want to obtain information about health service delivery and outputs without having to perform a review of all primary documents. The report also highlights the important issues and challenges related to diff erent aspects of the Ghanaian health system. In addition to this the report also provides historical information on the evolution of health service delivery in Ghana which is invaluable information for people involved in designing interventions to improve health in the country. The incubation period between the idea to have such a report and the delivery of the report has been long and we are happy that the final report is now out. The challenge that this publication now poses to the University of Ghana School of Public Health is to now ensure that there is regular and timely updating for the benefit of all the different groups who will make use of this first edition.
Research Report
Keywords: Nation; Health; Report; Ghana